New designed special cells for Raman mapping of the disintegration process of pharmaceutical tablets - Čapková-Helešicová, Tereza; Pekárek, Tomáš; Schöngut, Marek; Matějka, Pavel (Journal of pharmaceutical and biomedical analysis, 2019)
The goal of this study was the methodological development of Raman microscopy application for advanced and reliable monitoring of pharmaceutical tablets disintegration in aqueous media. First step of the development involved new design and testing of static, flow cell and tablet holders. On-line Raman mapping method enables observation of the tested tablet interphase changes, particularly the changes of tablet composition during interaction of the solid-state drug form with disintegration medium. Furthermore, the quantitative information of tablet components (% w/w) from Raman maps was calculated. Second part of this study performs off-line Raman mapping, which was focused on the mapping of disintegrated tablet residua. Time-dependent Raman chemical maps provide an understanding of the role of several synergic processes, e.g. solvation, solvent penetration, both active pharmaceutical ingredient and excipient dissolution etc., which occur simultaneously on the surface of dissolving tablet. Raman data of disintegration process were evaluated by a chemometric method - Principal Component Analysis (PCA).
Keywords: chemie farmaceutická; tablety; Drug Liberation; léčivé přípravky; Solvents; Spectrum Analysis, Raman; časové faktory; Excipients; Tablets; Chemistry, Pharmaceutical; Technology, Pharmaceutical; uvolňování léčiv; Ramanova spektroskopie; Pharmaceutical Preparations; farmaceutická technologie; pomocné látky; Principal Component Analysis; rozpouštědla; Time Factors; analýza hlavních komponent